Exercise intensity measurement using fractal analysis of heart rate variability: Reliability, agreement and influence of sex and cardiorespiratory fitness - Sheoran, S.; Stavropoulos-Kalinoglou, A.; Simpson, C.; Ashby, M.; Webber, E.; Weaving, D. (Journal of Sports Sciences, 2024)
The study aimed to establish the test-retest reliability of detrended fluctuation analysis of heart rate variability (DFA-a1) based exercise intensity thresholds, assess its agreement with ventilatory- and lactate-derived thresholds and the moderating effect of sex and cardiorespiratory fitness (CRF) on the agreement. Intensity thresholds for thirty-seven participants (17 females) based on blood lactate (LT1/LT2), gas-exchange (VT1/VT2) and DFA-a1 (aTh1/aTh2) were assessed. Heart rate (HR) at aTh1 and aTh2 showed good test-retest reliability (coefficient of variation [CV] < 6%), and moderate to high agreement with LTs (r = 0.40 - 0.57) and VTs (r = 0.61 - 0.66) respectively. Mixed effects models indicated bias magnitude depended on CRF, with DFA-a1 overestimating thresholds versus VTs for lower fitness levels (speed at VT1 <8.5 km·hr-1), while underestimating for higher fitness levels (speed at VT2 >15 km·hr-1; VO2max >55 mL·kg-1·min-1). Controlling for CRF, sex significantly affected bias magnitude only at first threshold, with males having higher mean bias (+2.41 bpm) than females (-1.26 bpm). DFA-a1 thresholds are practical and reliable intensity measures, however it is unclear if they accurately represent LTs/VTs from the observed limits of agreement and unexplained variance. To optimise DFA-a1 threshold estimation across different populations, bias should be corrected based on sex and CRF.